Guinea-Bissau : Selected Issues. (IMF Staff Country Reports; Country Report, 2015)
This Selected Issues paper aims at identifying some of the main channels of transmission through which political instability feeds and foster fragility and provide an estimate of the 'fragility gap' that haunts the Bissau-Guinean society. This paper argued that, until today, due to chronic political instability, Guinea-Bissau has been in a costly fragility trap. This analytical piece argues that the major factor behind Guinea-Bissau's fragility has been the chronic political instability. It also uncovers some of the main transmission channels from political instability to fragility and provides simple estimates about the cost of instability. Estimates based on reasonable assumptions reveal that, considering only Guinea-Bissau's post-war period, without chronic political instability real GDP per capita could have been at least two thirds higher than its 2013 level. This assessment shows the crucial importance of the security sector reform. It also shows that the current estimated cost of the security sector reform is modest in comparison, since it puts into perspective its monetary costs-which are easy to calculate and mostly frontloaded-vis-a-vis its wide and deep benefits, which are not as explicit and accrue over time.